Biological properties of rabbit antibodies to a surface antigen of Rickettsia rickettsii. - Anacker, R L (1983)
Because of the potential significance of external components of the obligate intracellular parasite Rickettsia rickettsii in host-parasite interactions, we have begun the first phase of a study to isolate and characterize surface antigens of this organism. An antiserum to a rickettsial surface component was obtained from rabbits inoculated with immune precipitates prepared by crossed immunoelectrophoresis of Triton X-100 extracts of R. rickettsii strain R. This antiserum (i) protected guinea pigs inoculated with 10,000 guinea pig 50% infectious doses of R. rickettsii against fever, (ii) prevented death of mice challenged with 2 50% lethal doses of R. rickettsii, and (iii) reacted in the microimmunofluorescence test with 9 of 13 spotted fever group serotypes tested. The location of this antigen on the rickettsial surface was demonstrated by immunoelectron microscopy with ferritin-labeled antibodies.